Pengaruh Kinerja Keuangan Terhadap Kebijakan Dividen Pada Perusahaan Telekomunikasi Saat Pandemi Covid-19 - Shalini, Witya; Hermiyetti; Tri Hartati Sukartini Hulu; Edison Sagala; Ratnawita (Owner : Riset dan Jurnal Akuntansi, 2024)
This study uses telecommunication companies as a research object because the pandemic does not affect this industry. Therefore, researchers want to see whether telecommunication companies can continue growing and surviving the COVID-19 pandemic. The method used in this study is a quantitative approach; the nature of the research is deductive, and samples selected with purposive sampling techniques. The population of this study was telecommunication companies listed on the Indonesia Stock Exchange 2020-2022 period. The research sample was 27 companies for 3 years, which was analyzed by a multiple linear regression analysis model. The study's results simultaneously showed that liquidity, leverage, and profitability affected the telecommunication companies' dividend policy on the Indonesia Stock Exchange in the 2020-2022 period by 52,2 %, the remaining influenced by other variables. Partially, the profitability affected the telecommunication companies' dividend policy on the Indonesia Stock Exchange in the period 2020-2022. Partially, liquidity and leverage do not affect profitability in the telecommunication companies' dividend policy on the Indonesia Stock Exchange in the 2020-2022 period.